Variable presentation of diabetic papillopathy and treatment dilemma- A case series (Nepalese Journal of Ophthalmology, 2020)
Introduction: Diabetic papillopathy (DP) is a diagnosis of exclusion in type 1 and type 2 diabetics with transient disc edema. It was initially described in young patients with type1 diabetes mellitus (DM) as a bilateral disease with minimal visual symptoms which resolved spontaneously. Lately, DP has been a focus of controversy because of its wide clinical spectrum.Cases: We describe three variable cases of DP. These are unilateral DP with Proliferative Diabetic Retinopathy (PDR) with macular edema (ME), unilateral DP with severe Non Proliferative Diabetic Retinopathy (NPDR) with ischemic maculopathy and a case of bilateral DP with Moderate NPDR with ME. We also discuss viable treatment for the variable presentation. DP has been reported in this case series in moderate NPDR, severe NPDR as well as PDR. Macular involvement in the form of macular edema as well as ischemia has been demonstrated to result in diminution of vision. It shows both unilateral and bilateral presentation. Remarkable visual loss seen, in these cases, call for intervention.Conclusions: DP has a wide spectrum of presentation and its knowledge is eminent to make a complete diagnosis. Individualisation of treatment has to be done for variable presentation and realistic outcomes should be explained to the patients.